Review of input and output policies for cereals production in Pakistan - Salam, Abdul (International Food Policy Research Institute, 2012)
The marketing of farm inputs and outputs has become a major problem for farmers in Pakistan. Farm input supplies are irregular, characterized by shortages and high prices at critical times. This report reviews the input and output policies for cereals implemented in Pakistan during the period 1996–2010. Pakistan has a long and varied history of intervening in farm input and output markets, going back decades before the period under review. Most significantly, in the wake of economic reforms launched during the 1980s, it has withdrawn from most of the commodity markets except wheat. In other commodity markets, intervention is by and large notional and without much practical involvement. The rolling back of the public sector from markets has certainly saved public funds, but the savings have come at a cost. Some of the cost, in terms of higher prices and variability stemming from the uncertain economic environment and supply, is borne by consumers, and some, in terms of lower producer prices at harvest, is borne by farmers, especially small and medium farmers, whose farms account for more than 50 percent of the area under cereals.